EDUCATING THE INFANT AND TODDLER (Author: Burton L. White) - Slaughter, Judith Pollard (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1989)
Burton L. White. EDUCATING THE INFANT AND TODDLER Lexington, MA: D.C. Heath and Company, 1988. 361 pp. $19.95.